2021
DOI: 10.2147/dddt.s291369
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Clinical Research on Gonadotropin-Releasing Hormone Receptor Antagonists for the Treatment of Prostate Cancer

Abstract: Gonadotropin-releasing hormone (GnRH) receptor agonists are still the most commonly used androgen deprivation treatment (ADT) drugs for prostate cancer in clinical practice. Currently, the GnRH receptor antagonists used for endocrine therapy for prostate cancer primarily include degarelix and relugolix (TAK-385). The former is administered by subcutaneous injection, while the latter is an oral drug. Compared to GnRH agonists, GnRH antagonists reduce serum testosterone levels more rapidly without an initial tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…11 The development of LHRH agonists and GnRH antagonists marked the beginning of a new era in the management of PCa. 12 While LHRH agonists cause an initial testosterone surge that may result in a clinical flare of symptoms, 13 GnRH antagonists have been shown to offer rapid reduction of serum testosterone without the initial testosterone surge and symptoms flare. 1 The Phase III HERO study revealed rapid testosterone suppression to castration levels with the first oral GnRH antagonist, relugolix, which were then maintained throughout the treatment period.…”
Section: Kurt Millermentioning
confidence: 99%
“…11 The development of LHRH agonists and GnRH antagonists marked the beginning of a new era in the management of PCa. 12 While LHRH agonists cause an initial testosterone surge that may result in a clinical flare of symptoms, 13 GnRH antagonists have been shown to offer rapid reduction of serum testosterone without the initial testosterone surge and symptoms flare. 1 The Phase III HERO study revealed rapid testosterone suppression to castration levels with the first oral GnRH antagonist, relugolix, which were then maintained throughout the treatment period.…”
Section: Kurt Millermentioning
confidence: 99%
“…These receptors associated with their ligands promoted migration, proliferation, neuroendocrine differentiation, mitogenic signaling and invasion of PC [ 61 ]. Some small molecules have been tested to block these GPCRs as antagonists of gonadotropin-releasing hormone receptor (GnRH), named degarelix or endothelin A receptor antagonist under clinical trial [ 54 , 62 ]. Inversely, few GPCRs and their ligands were able to inhibit growth of prostate cancer cells.…”
Section: Orexins and Other Cancersmentioning
confidence: 99%
“…Figure 1 represents some thienopyrimidinecontaining drugs with varying profiles of biological activity. Relugolix (TAK-385), is a thienopyrimidine derivative that has completed phase III clinical trials and is being studied for its capacity to treat endometriosis and prostate carcinoma by acting as a gonadotropin-releasing hormone receptor (GnRHR) antagonist [24,25]. DDP-225 is another thienopyrimidine drug that entered phase II clinical trials and was designed to cure irritable bowel syndrome (IBS) and gastrointestinal tract (GIT) diseases by acting as a serotonin receptor (5-HT 3 ) antagonist and noradrenaline reuptake inhibitor [26,27].…”
Section: Introductionmentioning
confidence: 99%